Effects of Laser Energy Density on Carbon‐Nanotube‐Reinforced Titanium Composites Printed via Selective Laser Melting. Issue 2 (27th August 2021) - DeMartino, Anthony; Ansell, Troy Y.; Nieto, Andy
Abstract : 3D‐printing‐reinforced metal matrix composites are a promising avenue for fabricating materials to meet the demands of the 21st century. Ti–6Al–4 V has been a useful material in the aerospace and medical industries for decades due to its incredible strength‐to‐weight ratio, and now its suitability for additive manufacturing has made it even more desirable. One of the leading‐edge reinforcements being studied for metal matrix composites is carbon nanotubes due to their remarkable mechanical properties such as strength and elastic modulus. It is desirable to manufacture advanced metal matrix composites using advanced manufacturing techniques such as selective laser melting. Herein, the effect of 1 vol% carbon nanotube reinforcements on the microstructural evolution and properties of selective‐laser‐melt‐printed Ti64 and the interrelationships with laser energy density, laser power, and laser scan speed are investigated. The effectiveness of reinforcement and influence of printing parameters are assessed via microstructural and porosity analysis, and microhardness testing. Utilizing selective laser melting with a laser energy density of 60 J mm −3, a >99% dense Ti–CNT composite is manufactured with microhardness of 4.75 GPa—a 30% enhancement over its Ti64 counterpart. Abstract : Herein, the enhancement of hardness with the incorporation of carbon nanotubes (CNTs) is shown. The strengthening mechanisms associated with the presence of CNTs are 1) grain refinement due to CNT pinning during 3D printing, 2) precipitation of titanium carbides due to partial reaction of CNTs with the Ti matrix, and 3) fiber reinforcement from the CNTs remaining after printing.